Pemberdayaan Masyarakat Desa dengan Usaha Kuliner Tradisional pada Kelompok Boga Ganesha Kabupaten Buleleng - MADE SUDANA; I GEDE SETIAWAN ADI PUTRA; NYOMAN PARINING (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2017)
The Village Community Empowerment With Traditional Culinary Business in the Group of Boga Ganesha Buleleng The development of fast food must be balanced with the consumption of traditional foods because fast food is allegedly to be a risk factor for the emergence of various diseases. This study aimed to analyze the behavior of IbIKK group of Boga Ganesha. The choice of location of the research was determined purposively with the consideration that the Boga Ganesha is one of the groups to empower the people with the traditional culinary efforts. The method used in collecting the data in this study was interviews with questionnaire instruments. Based on the research results, the potential of the IbIKK of Boga Ganesha is a kosher, hygienic and healthy traditional food processing. Behavior that was demonstrated by the members can be classified into an excellent category (4,6). The achievement of the implementation of the empowerment program that is included in the category of successful (4,2). Empowerment of program aimed to improve the quality of human resources. In this regard, members of the group should implement their skills so that they can open up business opportunities in order to improve the economy of the family. To support this, the facilitator should use the appropriate method so that all participants can obtain information equally.